Mutual Role Expectations by Patients and General Practitioners-A Mixed Methods Study on Complementarity - Plagg, Barbara; Engl, Adolf; Piccoliori, Giuliano; Atz, Hermann; Becker, Ulrich; Kiem, Johann; Barbieri, Verena; Eisendle, Klaus; Wiedermann, Christian Josef; Elsen, Susanne Ursula; Lorenz, Walter August (Healthcare, 2022)
BACKGROUND: Changes in public attitudes toward "authorities" in general, as well as shifts in medical practice toward participative models of diagnosis and treatment, imply fundamental transformations in the patient-doctor relationship. However, consistency in reciprocal role expectations cannot be assumed, and this study reveals significant discrepancies in attitudes and behaviors in primary health consultations. METHODS: We conducted a study in the tri-lingual northeastern Italian region of South Tyrol to determine whether perceptions of the patient's role were congruent or differed. In a mixed method approach, the quantitative research part consisted of a survey with 34 identical questions for general practitioners (n = 109) and adult primary care patients (n = 506) on verbal communication, self-initiative and health literacy, interpersonal and social qualities of the patient-physician relationship, and formal aspects of the consultation. Patients were interviewed via telephone, and general practitioners responded online. In the qualitative part, 26 semi-structured in-depth interviews were conducted with the patients and analyzed. RESULTS: General practitioners considered patients' communicative efforts (p < 0.001), self-initiative (p < 0.001), compliance (p = 0.0026), and openness regarding psychosocial issues (p < 0.001) to be significantly more important, whereas patients showed a tendency to give increased importance to formal aspects such as politeness and hygiene (p < 0.001). Perception of the patient's role differed significantly between the Italian and German linguistic groups. CONCLUSIONS: Patients and general practitioners differ in their understanding of patients' roles. These data suggest that a considerable proportion of the population lacks a clear and tangible idea of the active role they could play in consultations. Targeted information on the identified aspects of patient-provider communication may facilitate participatory behavior and positively impact the longitudinal quality of the patient-general practitioner relationship.